PENGUJIAN VALIDITAS MODEL CAPM BETA, MODEL TIGA FAKTOR FAMA â FRENCH, DAN MODEL EMPAT FAKTOR CARHART PADA PASAR MODAL INDONESIA - , FEBRIYANTI DIMAELITA SIAGIAN, Prof. Dr. Jogiyanto HM., MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to test the validity of CAPM beta model, Fama â Frenchâs three-factor model, and Carhartâs four-factor model to explain the relation between risk and return in the Indonesian stock market. CAPM beta model proxied by measuring the influence of beta to stock returns. Fama â Frenchâs three-factor model proxied by measuring the influence of beta, size, and book to market equity ratio to stock returns. Carhartâs four-factor model proxied by measuring the influence of beta, size, book to market equity ratio, and momentum to stock returns. Samples used in this study is all companies listed on the Indonesia Stock Exchange (IDX) with 2006 up to 2011 as the observation period. The total sample was different every observations year with the aim, that data used could describe the real market conditions, are determined by the method of purposive sampling. This study uses an ordinary least square to examine the effect of beta, size, book to market equity, and momentum to stock returns. The results of this study indicate that the CAPM beta model, Fama â Frenchâs three-factor model, and Carhartâs four-factor model are valid for using in the Indonesian stock market and able to explain the relation between risk and return in the Indonesian stock market.